High frequency ultrasonography of the facial nerve: Another effective method to observe the course of idiopathic facial nerve paralysis - Jing Zhu; Xiaohua Li; Yang Han; Yu Cao; Longfei Guan; Xiaokun Geng (Wolters Kluwer Medknow Publications, 2020)
Objective: This study was designed to investigate and compare both ultrasonographic and electrophysiological methods of examination of the facial nerve in idiopathic facial paralysis (IFP). Materials and Methods: Patients with IFP diagnosed between January 2018 and June 2019 (n = 178) underwent ultrasonographic and electrophysiological examinations of the facial nerve, within the 1st week of symptoms and every 1-3 following weeks until asymptomatic, with comparisons between the affected and unaffected sides. Results: There were significant differences in the ultrasonographic diameter and the electrophysiological results obtained from the facial nerve between the affected and unaffected sides. Ninety-one patients completed follow-up and underwent re-examination of the facial nerve by ultrasonography and/or electromyography. The difference between the affected and unaffected sides in terms of the ultrasonographic diameter of the facial nerve gradually decreased with the course of the disease. The ultrasonographic diameter of the facial nerve of the affected side was greater by 0.3 mm than that of the unaffected side for more than 3 weeks, indicative of a poor prognosis, which was consistent with the electrophysiological results. Conclusions: The combination of ultrasonographic and electrophysiological examinations of the facial nerve serves to better guide clinical treatment and assess the prognosis of IFP.